Strategi Manajemen Waktu untuk Peningkatan Kinerja Pegawai di Sekretariat Jenderal DPD RI - Pusfitasari, Dwi (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: The Secretariat General of the DPD RI faces complex challenges such as a heavy workload, time constraints, and cross-work unit coordination, which frequently causes workflow congestion. This has an impact on the delay of the Secretariat General's main task, which is to assist the DPD RI's constitutional duties, due to overlapping priorities caused by poor time management. Methodology/approach: . The implementation of Activity-Based Management (ABM) serves as a strategic solution for identifying and eliminating unproductive activities, whereas the Eisenhower Matrix, 4D Method, and Kanban Method are critical for establishing urgent and strategic task priorities Results/findings: . The combination of these four approaches is expected to not only increase operational efficiency and reduce delays, but also to ensure consistent service quality while supporting the DPD RI's constitutional duties holistically. Conclutions: The transformation of time management is expected to strengthen institutional capacity to respond to the dynamics of dynamic legislative tasks while maintaining consistent quality of public services on an ongoing basis. Limitations: The study's main limitation is that it only looks at the Secretariat General of the DPD RI, which has its own unique characteristics as a supporter of the DPD RI. The findings and recommendations may not be completely applicable to other government institutions, due to differences in hierarchical structures, bureaucratic cultures, and task complexity. Contribution: . The study's findings highlight the importance of time management integration as a strategic foundation for improving operational efficiency and performance effectiveness.